Investigation on the difference of PM2.5 transport flux between the North China Plain and the Sichuan Basin. (15th February 2022) - Zhang, Zhida; Wang, Xiaoqi; Cheng, Shuiyuan; Guan, Panbo; Zhang, Hanyu; Shan, Changgong; Fu, Yibin
Abstract: In this study, an advanced transport flux method based on the comprehensive stereoscopic observation verification was used to evaluate the contribution of transport to pollution in the North China Plain (NCP) and Sichuan Basin (SCB). The simulations were verified using fixed-point lidar and satellite observations, and the results demonstrated that the modeling flux calculation method was suitable for investigating the evolutionary trend of PM2.5 flux. The monthly inflow, outflow, and net flux indicated the intensive interactions and significant temporal and spatial variations of PM2.5 transport though the boundary segment of the city and region. In both autumn and winter, the Beijing-Tianjin-Hebei (BTH) region always played the role of "source" region, while Cheng-Yu (CY) region principally acted as a "convergence" region. In autumn and winter, the BTH region was controlled by a cold front weather system, and the pollutants were readily transported to the surrounding areas. However, the CY region was affected by the complex terrain, with small wind speeds near the ground and poor horizontal diffusion. The upper air was controlled by the northwestern winds behind the trough, and the air subsidence is substantial. The combined action of horizontal and vertical wind directions caused the accumulation of pollutants in the basin. Notably, one intrinsic transport pathway during two representative months was identified based on the investigation of cross-city and cross-region transport, namely the southwest–northeast (SW–NE) pathway in the BTH region. In the CY region, the northeastern transport pathway greatly influenced the cities in the basin. Additionally, through the analysis of the typical heavy pollution processes in the two regions, it was found that the southwest pathway of the BTH region and northeast pathway of the CY region in inter-city transport were significant factors before reaching the most severe stage of pollution. Highlights: The BTH region always played the role of "source" region. The CY region acted as a "convergence" region due to the complicated topography. Three major PM2.5 transport pathways were identified. The BTH region were related to the transport from the surrounding regions. The CY region were greatly affected by the inter-basin transport.